Pengggunaan Metode FIFO Dan FEFO Dalam Mengukur Efisisensi Dan Efektifitas Persediaan Obat Paten 2020-2021 - Yudi Siyamto (Jurnal Ilmiah Ekonomi Islam, 2022)
Drugs are an important part of health services, so they require proper, effective and efficient management in a sustainable manner. The purpose of this research is to determine the efficiency and effectiveness of patent drug inventory management using FIFO and FEFO methods. This research uses quantitative research with a descriptive approach, with a sample of 127 patented drugs. The analysis used is the calculation of the inventory turn over ratio. The results show that the use of the FIFO and FEFO methods can be said to be effective and efficient with the resulting value in 2020 of 63.78% and 2021 of 68.50%, where the value is greater than the results of the ineffective and efficient category with the value of 2020 by 36.22% and in 2021 by 31.50%.